Cyclohexylammonium nitrate - A. Bagabas, Abdulaziz; Aboud, Mohamed F. A.; Shemsi, Ahsan M.; Addurihem, Emad S.; Al-Othman, Zeid A.; C. S., Chidan Kumar; Fun, Hoong Kun (International Union of Crystallography, 2014)
In the title salt, C6H14N+.NO3_, the cyclohexyl ring adopts a chair conformation. The ammonium group occupies an equatorial position and the crystal struture is stabilized by intermolecular N—H O hydrogen-bonding interactions, resulting in a three-dimensional network.